(untitled) (Czech Journal of International Relations, 2019)
Around the world, people who are angry at stagnant wages and growing inequality have rebelled against established governments and turned to political extremes. Liberal democracy, history’s greatest engine of growth, now struggles to overcome unprecedented economic headwinds–from aging populations to scarce resources to unsustainable debt burdens. Hobbled by short-term thinking and ideological dogma, democracies risk falling prey to nationalism and protectionism that will deliver declining living standards. In Edge of Chaos, Dambisa Moyo shows why economic growth is essential to global stability, and why liberal democracies are failing to produce it today. Rather than turning away from democracy, she argues, we must fundamentally reform it. Edge of Chaos presents a radical blueprint for change in order to galvanize growth and ensure the survival of democracy in the twenty-first century.